Feminist Movements in Time and Space
XI, 311 p. 3 illus.
Keywords: This volume provides a broad analysis of feminist movements--both historical and present-day--in Europe. It will fill the gap in the literature on feminist mobilizations through a systematic analysis of European third wave feminism from a cross-national perspective (covering Denmark, France, Greece, Italy, Poland, Slovenia, Spain, and Turkey) and a cross-time perspective (covering the time frame 2010-2021). In doing this, the authors also single out the different constellations of feminist movements as related to specific national political opportunities and networks of alliance and opposition. This book will be of interest to students and scholars in gender studies, feminist theory, and social movement studies. Giada Bonu Rosenkranz is a post-doctoral research fellow in the Horizon project "FIERCE. Feminist movements revitalizing democracy in Europe," at the Scuola Normale Superiore where she is part of the Center on social movement studies (cosmos). Donatella Della Porta is professor of political science, founding dean of the Faculty of Political and Social Sciences and Director of the PhD program in Political Science and Sociology at the Scuola Normale Superiore in Florence, where she also leads the Center on social movement studies (cosmos).